A(H1N1)pdm09 hemagglutinin D222G and D222N variants are frequently harbored by patients requiring extracorporeal membrane oxygenation and advanced respiratory assistance for severe A(H1N1)pdm09 infection - Ruggiero, Tina (Influenza Other Respir Viruses, 2013)
BACKGROUND: In patients with A(H1N1)pdm09 infection, severe lung involvement requiring admission to intensive care units (ICU) has been reported. Mutations at the hemagglutinin (HA) receptor binding site (RBS) have been associated with increased virulence and disease severity, representing a potential marker of critical illness. OBJECTIVES: To assess the contribution of HA‐RBS variability in critically ill patients, A(H1N1)pdm09 virus from adult patients with severe infection admitted to ICU for extracorporeal membrane oxygenation support (ECMO) during influenza season 2009–2011 in Piemonte (4·2 million inhabitants), northwestern Italy, was studied. PATIENTS AND METHODS: We retrospectively analyzed HA‐RBS polymorphisms in ICU patients and compared with those from randomly selected inpatients with mild A(H1N1)pdm09 disease and outpatients with influenza from the local surveillance program. RESULTS: By HA‐RBS direct sequencing of respiratory specimens, D222G and D222N viral variants were identified in a higher proportion in ICU patients (n = 8/24, 33·3%) than in patients with mild disease (n = 2/34, 6%) or in outpatients (n = 0/44) (Fisher's exact test P < 0·0001; OR 38·5; CI 95% 4·494–329·9). Eleven ICU patients died (42%), three of them carrying the D222G variant, which was associated with RBS mutation S183P in two. D222G and D222N mutants were identified in upper and lower respiratory samples. CONCLUSIONS: A(H1N1)pdm09 HA substitutions D222G and D222N were harbored in a significantly higher proportion by patients with acute respiratory distress for A(H1N1)pdm09 severe infection requiring ICU admission and ECMO. These data emphasize the importance of monitoring viral evolution for understanding virus–host adaptation aimed at the surveillance of strain circulation and the study of viral correlates of disease severity.